Validation of nursing outcome content Fall prevention behavior in a hospital environment - Jéssica Naiara de Medeiros Araújo; Ana Paula Nunes de Lima Fernandes; Laísla Alves Moura; Marina Marisa Palhano dos Santos; Marcos Antonio Ferreira Júnior; Allyne Fortes Vitor (Rev Rene)
Objective: to validate the contents of the nursing outcome Fall prevention behavior of the Nursing Outcomes Classification in hospitalized patients. Methods: this is a content validation research. Psychometry was used as an operational method. The Nursing Outcome was validated by 16 specialists. A Content Validity Index was applied with its binomial test to evaluate the indicators in the psychometric criteria. Results: from the experts’ assessment of the constitutive, operational and operational magnitude of the indicators, the need for adequacy was found in the indicators. It controls the restlessness, it carries out precautions when taking drugs that increase the risk of falls and it adequately use chairs. Conclusion: it was found that the indicators were considered mostly valid as to the content. Therefore, they were able to measure the prevention behavior of fallsin the hospital environment.